Combustion analysis of CuO2 nanoparticles addition with neochloris oleoabundans algae biodiesel on CI engine. (2020) - Kalaimurugan, K.; Karthikeyan, S.; Periyasamy, M.; Dharmaprabhakaran, T.
Abstract: An experimental research is performed to determine the performance, combustion as well as emission qualities of a variable compression engine at constant speed using Copper Oxide nanoparticles as being fuel-borne additives in diesel–biodiesel blend. In this research, the effects of adding CuO2 nanoparticles to neochloris oleoabundans methyl ester-diesel blended (B20) fuel on compression-ignition engine had been experimentally investigated. The B20 with 25, 50, 75, and 100 ppm dosage of CuO2 nanoparticles were examined at various engine loads and constant engine speed. The fuel blends were labelled as B20, B20 + 25 ppm, B20 + 50 ppm, B20 + 75 ppm and B20 + 100 ppm. Moreover, even without the any engine alterations, the combustion properties of those fuel blend samples were investigated through the experimentally measured standards like viscosity, density, cloud point, calorific value and pour point while the engine combustion has also been examined through the factors like cylinder pressure, net heat release as well as rate of pressure rise. The experimental outcomes show that the use of biodiesel blend along with CuO2 nano particles in diesel fuelled engine has revealed better combustion than B20 fuel.